The Role of Green Entrepreneurship as an Innovative Strategy in Addressing the Environmental Crisis - Suci Cahyati; Chairia Chairia; Hendra Sakti Putra Siagian; Dina Meilisa (Entrepreneurship Faculty, Universitas Garut, 2025)
The escalating environmental crisis has demanded not only policy reform and technological advancement, but also a fundamental shift in the way economic value is created. This study explores green entrepreneurship as a transformative and innovative strategy to address ecological degradation while fostering sustainable economic growth. Through a multidisciplinary lens, we conceptualize green entrepreneurship not merely as environmentally friendly business practices, but as a disruptive force capable of reconfiguring market dynamics, consumer behavior, and socio-ecological systems. Drawing upon emerging frameworks in sustainable innovation and systems thinking, this paper proposes a novel typology of green entrepreneurial models that integrate circular economy principles, community-based innovation, and regenerative practices. Our analysis reveals that green entrepreneurs are uniquely positioned to bridge institutional gaps, catalyze grassroots movements, and scale systemic solutions to environmental challenges. The study concludes with policy recommendations aimed at fostering an enabling ecosystem for green entrepreneurship as a core pillar in the transition toward a low-carbon, resilient, and inclusive economy.